Political economy of India`s north-east border (New Delhi, 2015)
This book examines the various aspects of human development in North-East India. Covering sixteen districts across six states: Assam, Meghalaya, Mizoram, Nagaland, Arunachal Pradesh and Tripura, it makes an analytical study of the indicators of human development in the region, with special focus on different socio-economics, linguistic and ethnic groups. Taking a close look at the present scenario of education and health status, it deals with the quality of life and the nature of the occupation of the people of the region. Finally, it examines the Human Development Index for the various socio-economic and religious groups of the people. The book will be of immense use for students, researchers, policy-makers and development workers.
Keywords: "India, Northeastern"